A soft approach to management of information security. - Armstrong, Helen (Curtin University, 1999)
The key theme of this research is the planning and management of information security and in particular, the research focuses on the involvement of information stakeholders in this process. The main objective of the research is to study the ownership of, and acceptance of responsibility for, information security measures by stakeholders having an interest in that information.